(untitled) (Update Dental College Journal, 2014)
Mandibular molars often have an additional root located lingually (the radix entomolaris) or buccally (the radix paramolaris). If present, an awareness and understanding of this unusual root and its root canal morphology can contribute to the successful outcome of root canal treatment. This report discusses endodontic treatment of a mandibular molar with a radix entomolaris, which is a rare macrostructure. The prevalence, the external morphological variations and internal anatomy of the radix entomolaris are described. Avoiding procedural errors during endodontic therapy demand an adapted clinical approach to diagnosis and successful non-surgical endodontic treatment. DOI: http://dx.doi.org/10.3329/updcj.v3i1.17986 Update Dent. Coll. j: 2013; 3 (1): 49-53